Penapisan Hipertensi melalui Pelayanan Pengukuran Tekanan Darah bagi Warga Desa Kampung Baros Ciherang Pacet Paska Bencana Gempa Cianjur - Alexander Halim Santoso; Octavia Dwi Wahyuni; Twidy Tarcisia; Denny Denny (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Geographically, the archipelago Indonesia is located on the Ring of Fire which is the meeting point of many tectonic plates. This condition causes Indonesia to be prone to earthquakes. The West Java Cianjur earthquake in November 2022 was a 5.6 MW earthquake with a depth of 10 km, which was caused by the movement of the Cugenang fault. Ciherang Village in the Pacet sub-district, Cianjur is one of the villages affected by the Cianjur earthquake. Victims of natural disasters are physically, psychologically and socially faced with very complex situations and circumstances. These problems cause stress for all residents and can cause hypertension. The purpose of this Community Service activity is to help ease the mental burden of Ciherang villagers who were affected by the earthquake. It is hoped that through this blood pressure measurement activity, the hypertension status of residents can be known. The results of blood pressure measurements showed that 9.7% had high blood pressure (130-139/85-89 mmHg) and 37.1% of residents had hypertension (≥140/90 mmHg).